Reasoning like a doctor or like a nurse? An integrative review protocol - Rashmi A Kusurkar; Jos Dobber; Jettie Vreugdenhil; Sunia Somra; Hans Ket; Eugène J F M Custers; Marcel E Reinders (BMJ Open)
Introduction Clinical reasoning, a major competency for all health professionals, has been defined and studied ‘within’ each profession. We do not know if content, process and outcomes are comparable ‘between’ physician and nursing clinical reasoning. This paper aims to set up a protocol for an integrative review to analyse and synthesise the scientific nursing and medical clinical reasoning literature. It builds on the history of nursing and medical clinical reasoning research and aims to create a higher level of conceptual clarity of clinical reasoning, to increase mutual understanding in collaboration in patient care, education and research.Methods and analysis This integrative review follows stepwise the methods described by Whittmore and Knafl: problem identification, literature search, data evaluation, data analysis and presentation.The initial systematic and comprehensive search strategy is developed in collaboration with the clinical librarian and is performed in electronic databases, PubMed, CINAHL, PsycInfo and Web of Science from 30 March 2020 to 27 May 2020. Empirical and theoretical studies are included. This search will be accompanied by ancestry searching and purposeful sampling. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow chart will summarise the selection process. The quality of eligible studies will be evaluated with a checklist, suitable for diverse study methods.The data analysis is inspired by concept analysis of Walker and Avant and layered analysis of an intervention of Cianciolo and Regehr. We will extract the data of the included studies conforming these layers and features, to capture the multifaceted nature of clinical reasoning in both professions. The data will be presented in a validity matrix to facilitate comparing and contrasting.Ethics and dissemination Ethics approval is not required. The outcomes will be disseminated through conference presentations and publications.